LDL cholesterol targets--how low to go? - Bulbulia, R; Armitage, J (2012)
PURPOSE OF REVIEW: Lowering LDL cholesterol (LDL-C) reduces vascular risk. Current guidelines recommend initiating statin therapy in patients with a yearly coronary heart disease risk of around 1.5-2%, and most clinicians prescribe standard statin regimens (e.g. 40 mg simvastatin daily). However, there is some uncertainty about whether patients at somewhat lower vascular risk should receive lipid-lowering therapy and also how intensive statin treatment should be. RECENT FINDINGS: Lowering LDL-C by around 1 mmol/l reduces vascular mortality and major morbidity by about one-fifth, and more recent randomized trials comparing intensive versus standard statin regimens confirm that a further LDL-C reduction of 0.5 mmol/l results in an additional 15% reduction in the risk of a major vascular event. Furthermore, statin therapy significantly reduces vascular mortality and morbidity in patients with less than 1% annual risk of a major vascular event. In general, statins are safe and well tolerated, but 80 mg simvastatin is associated with an unacceptably high risk of statin-induced myopathy. SUMMARY: Lipid-lowering therapy with statins is cost-effective for a wider range of patients than currently recommended. Intensive statin therapy is associated with larger reductions in vascular risk, and lower LDL-C targets (particularly for higher-risk individuals) should help reduce vascular mortality and major vascular morbidity substantially.